Penilaian Pengetahuan, Keterampilan, dan Sikap Peserta Pelatihan Implementasi Sistem Jaminan Halal di Usaha Mikro dan Kecil Pangan - Sucipto Sucipto; Alda Alvita; Luki Hidayati; Muhammad Arif Kamal; Retno Astuti; Nur Hasanah (JURNAL AGROINDUSTRI HALAL, 2021)
Micro and Small Enterprises (MSEs) in Batu city, East Java, have developed, but many have not yet applied for halal certification. One of the efforts to encourage the MSEs halal certification submission is the Halal Assurance System (HAS). The problem is that the HAS training program has not been widely available and has not been assessed for success. This study aimed to assess the training program of HAS implementation for MSEs judging by the satisfaction, knowledge, skills, and attitude of the trainees. Assessment using Kirkpatrick method, level 1 assessments use questionnaires related to trainees satisfaction and level 2 relates to the learning process to change knowledge, skills, and attitudes. The respondents were 17 of local food MSEs. Data analysis using Wilcoxon Test for level 2. The results showed that trainees were satisfied with overall training implementation. Pre-test and post-test results of knowledge, skills, and attitudes aspects differed significantly and improved. The HAS implementation training program can improve respondents' knowledge and attitude in aspects of raw materials, products, production processes, production facilities, storage and handling of materials and products, and improved overall skills. HAS implementation training needs to be continuously developed to support the halal guarantee of food products MSEs.